DEVELOPMENT OF INTELLIGENT WEB APPLICATIONS FOR AUTONOMOUS CONTROL OF ROBOTIC DEVICES (IN THE FORM OF MULTIDIMENSIONAL OBJECTS) IN THE AGRICULTURAL SECTOR (Journal of Problems in Computer Science and Information Technologies, 2024)
Global agricultural challenges, including those faced in Azerbaijan, encompass climate change, water scarcity, irrigation difficulties, soil degradation, biodiversity loss, rising production costs, market uncertainty, labor shortages, and concerns around food safety and quality. These issues pose significant obstacles to the sustainable development of agriculture and demand innovative solutions. Climate change, for instance manifested – in rising temperatures and increased extreme weather events – creates an uncertain and often unfavorable environment for farmers. In Azerbaijan, the Presidential Decree dated July 15, 2021, on measures to promote agricultural production and processing, has established favorable conditions for the effective deployment of smart web applications designed for intelligent agricultural process control, as discussed in the article. The article explores several key areas of this decree, aligning them with the objectives of advancing smart technologies in agriculture. These proposed web-based solutions aim to enhance the automation, improvement, and efficiency of agricultural processes, and they are well-supported by government policies and incentives aimed at stimulating Azerbaijan’s agricultural sector.
Keywords: web application; mechatronic robotic devices; UX/UI design; agricultural sector; intelligent web applications; multidimensional objects; smart farming